ROLE OF PROPHYLACTIC GATIFLOXACIN IN LAPAROSCOPIC CHOLECYSTECTOMY – A COMPARATIVE STUDY WITH CEFTRIAXONE - Anjna; Kundra, Tanveer Singh; Kaur, Jaspreet; Garg, Lalit Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The objective of this study was to evaluate and compare the effectiveness of gatifloxacin and ceftriaxone as prophylactic antibiotic in elective clean surgical procedures. Methods: Sixty patients, undergoing laparoscopic cholecystectomy, were recruited consecutively and divided into two groups, that is, Group A and Group B of 30 patients each. In Group A, a pre-operative dose of injection ceftriaxone 1 g was administered intravenously half an hour before induction of anesthesia and second dose was given 12 h postoperatively. In Group B, pre-operative dose of tablet Gatifloxacin 400 mg was administered night before operation and another tablet postoperatively when the patient started orally in the evening. If not accepting orally then single intravenous infusion of Gatifloxacin was given in the evening. Results: In Group A, one patient (3.33%) had grade 1 and two patients (6.66%) had grade 2 infection. Similarly in Group B, one patient (3.33%) had grade 1 and two patients (6.66%) had grade 2 infection. None of the patients in both the groups had severe post-operative wound infection (grade 3 and grade 4). Conclusion: Prophylactic gatifloxacin is non-inferior to the “current gold standard ceftriaxone” as far as effectiveness of the drug is concerned. In addition, it had a similar side effect profile and was equally safe as a prophylactic antibiotic in preventing wound infection following routine elective laparoscopic cholecystectomy.